Hubungan antara Optimisme dengan Kualitas Hidup pada Pasien Lupus Eritematosus - Akrim Permitasari; Arief Nurudhin; Bagus Wicaksono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Systemic Lupus Erythematosus (SLE) is an auto-immune disease that is vary since its relapse period (flare) and remission period. The occurence of flare on SLE consist of many factors, one of them is depression that is caused by stress. While, the optimists are known as people who have good ability on dealing with stress. This research is aimed to find out the relation between optimism and living quality of patients who suffered from SLE. Research Method: This research was an analytic observational research with cross sectional approach. The sample was SLE patients who are fused in Griya Kupu Surakarta community. This research conducted by filling out the quetionnaires, optimism quetionnaire (Life Orientation Test-Revised) and quality of life quetionnaire (SF-36). From these two data, the researcher did the analysis using Pearsons product moment correlation analysis. Then, the data were treated by using SPSS 14,0 for Windows application. Result: Based on the analysis, there were some result obtained: there was a strong unidirectional relation (r = 0,613) and significant (sig = 0,000) between optimism and quality of life. There was varied relationship between optimism and quality of life on each domain. Optimism had strong unidirectional relation on physical function domain (r = 0,515, sig = 0,003), pain domain (r = 0,570, sig = 0,001), social function domain (r = 0,602, sig = 0,000) and general health (r = 0,614, sig = 0,000). Optimism had quite strong unidirectional relation with physical role domain (r = 0,329, sig = 0,071), the role of emotion domain (r = 0,429, sig = 0,016) and energy domain (r = 0,498, sig = 0,004). But, on physical role domain (sig = 0,071) this result was not significant. Optimism had inversely relation with mental health (r = -0,318, sig = 0,087), this result was not significant. Conclusion: Based on this research, it can be concluded that there is a strong relation (r = 0,613, sig = 0,000) between optimism and quality of life of Systemic Lupus Erythematosus patients. Key Words: Systemic Lupus Erythematosus, Optimism, Quality of Life